Igniting the flame, maximizing energy: The effectiveness of nutmeg oil as a bioadditive in B20 droplet combustion - Rachmat Subagyo; Mastiadi Tamjidilah; Abdul Ghofur; Rudi Siswanto; Ma'ruf Ma'ruf; Wardoyo Wardoyo; Muchsin Muchsin; Purnomo Purnomo; Atma Cahyo Anggono; Faisal Fadillah; Anugrah Perdana Putra (Universitas Muhammadiyah Magelang, 2025)
This study aims to experimentally investigate the effect of adding nutmeg oil (Myristica fragrans) as a bioadditive on the combustion characteristics of Biosolar B20 fuel droplets, addressing its inherent drawbacks such as longer ignition delay and incomplete combustion. Nutmeg oil iss selected due to its high oxygenated compound content and potential to enhance combustion efficiency and ignition quality. Key parameters examined include ignition delay time, combustion duration, burning rate, flash point, flame height, and peak temperature during the combustion process. Nutmeg oil was added in volumes ranging from 1 to 5 mL to the B20 mixture, and the combustion experiments were carried out using a droplet-based method to observe ignition and burning behavior under controlled conditions. The results showed that the addition of nutmeg oil significantly reduced the ignition delay time from 6.74 seconds (pure B20) to 1.38 seconds (5 mL nutmeg oil), along with decreases in combustion duration and flash point. Conversely, the burning rate increased from 0.53 mm²/s to 1.04 mm²/s, and the maximum temperature rose from 409.4°C to 553.3°C. GC-MS analysis revealed an increase in active volatile compounds such as α-pinene and myristicin, which enhanced the combustion process. ANOVA and Tukey HSD statistical tests confirmed that the differences among treatments were statistically significant (p < 0.05). Overall, this study highlights the potential of nutmeg oil–blended B20 fuel for practical engine applications and its contribution to sustainable energy development.